Efektivitas Sistem Kearsipan Dinamis (SIKD) Sebagai Sarana Temu Kembali Arsip di Dinas Arsip, Perpustakaan dan Dokumentasi (ARPUSDOK) Kota Palembang - Mulyadi Mulyadi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2018)
A benchmark for the progress of a filing institution is when the user is already using an information technology service (computer) in this case performing archive search services using the Dynamic Filing System (SIKD). And in the era of the information technology era all the services have been done electronically by using the computer, because the service manual is no longer relevant in the present, because it takes a lot of time, energy, mind, place etc. Using the archive service will find it easy. Seeing from the background there is a problem that is how the system of service implementation, the level of effectiveness in finding the archives in the Archives, Library, and Documentation Office (ARPUSDOK) of Palembang. Which will be examined by the team is the extent to which the effectiveness of services in terms of retrieval archive by looking at recall (acquisition) with precision (accuracy) in searching the archive in the archive library and documentation of the city of Palembang. This study aims to determine the application and effectiveness of services in terms of retrieval archives made by users who visit the archives library and documentation of the city of Palembang. This research is qualitative research. The data source can be through observation, in-depth interview, and documentation method. This study was analyzed by reducing data, presenting data, verifying and drawing conclusions. From the results of research conducted is known that in terms of information retrieval or recall (recall) is to check the number of acquisition of Dynamic Filing System (SIKD) Arpusdok Agency City of Palembang 55%. While the precision (precision) is the number of relevant collections found on the shelf with the number of collections obtained in the system the result is about 50%. So it can be concluded still felt less effective due to the lack of trace means therefore needed synergy between the system and the existing arrangement coupled with the means and infrastructure needed in the search. Then the obstacle faced is because this system is already offline then the existing cable network is still not adequate so that serious handling from all parties. Tolak ukur kemajuan sebuah lembaga kearsipan adalah ketika pengguna itu sudah menggunakan layanan teknologi informasi (komputer) dalam hal ini melakukan layanan penelusuran arsip dengan menggunakan Sistem Kearsipan Dinamis (SIKD). Dan di zaman era teknologi informasi semua layanan sudah dilakukan secara elektronik dengan menggunakan komputer, karena layanan manual sudah tidak relevan lagi di masa sekarang ini, karena banyak menyita waktu, tenaga, fikiran, tempat dll. Dengan menggunakan layanan arsip akan menemukan kemudahan. Melihat dari latar belakang tersebut muncul sebuah permasalahan yaitu bagaimana sistem penerapan layanan, tingkat keefektivitasan dalam menemukan arsip di Dinas Arsip, Perpustakaan, dan Dokumentasi (ARPUSDOK) kota Palembang. Yang akan diteliti adalah sejauh mana efektivitas layanan dalam hal temu balik arsip dengan melihat recall (perolehan) dengan precision (ketepatan) dalam mencari arsip yang ada di dinas arsip perpustakaan dan dokumentasi kota palembang. Penelitian ini bertujuan untuk mengetahui penerapan dan efektivitas layanan dalam hal temu balik arsipi yang dilakukan oleh pengguna yang berkunjung ke dinas arsip perpustakaan dan dokumentasi kota palembang.Temuan dari penelitian ini adalah bahwa masih dirasakan kurang efektif dikarenakan masih sedikitnya sarana penelusuran oleh karena itu dibutuhkan sinergisitas antara sistem dan penyusunan yang ada dibarengi dengan sarana dan prasarana yang dibutuhkan dalam penelusuran tersebut. Kemudian kendala yang dihadapi adalah karena sistem ini sudah ofline maka jaringan kabel yang ada masih belum memadai sehingga perlu penanganan yang serius dari semua pihak